2012
DOI: 10.1002/ejlt.201100176
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of refined olive oil by enrichment with chlorophyll pigments extracted from Chemlali olive leaves

Abstract: This paper presents the first investigation on the effect of enrichment refined olive oil by chlorophyll pigment extracted from Chemlali olive leaves during storage (6 months). The changes that occurred in the quality indices, fatty acids, sterol, and phenolic content were investigated during the storage of refined olive oil under RT (208C) and accelerated conditions (508C) in the dark. Additionally, the pigments (chlorophyll and carotene) changes during 6 months of oil storage were evaluated. At the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 27 publications
7
20
0
Order By: Relevance
“…While in olive oil enriched with olive leaves and basil extracts, the losses of carotenoid content was 57 and 55 %, respectively, from the initial content. The results of the present study are in accordance with Jaber et al [19] who studied the stabilization of refined olive oil by enrichment with chlorophyll pigments extracted from Chemlali olive leaves. In addition, these results were in agreement with those founded by Malheiro et al [17] and Yahyaoui et al [2] who reported that microwave heating time decreased the total chlorophylls and carotenoids contents as long as the exposure time increases.…”
Section: Resultssupporting
confidence: 93%
“…While in olive oil enriched with olive leaves and basil extracts, the losses of carotenoid content was 57 and 55 %, respectively, from the initial content. The results of the present study are in accordance with Jaber et al [19] who studied the stabilization of refined olive oil by enrichment with chlorophyll pigments extracted from Chemlali olive leaves. In addition, these results were in agreement with those founded by Malheiro et al [17] and Yahyaoui et al [2] who reported that microwave heating time decreased the total chlorophylls and carotenoids contents as long as the exposure time increases.…”
Section: Resultssupporting
confidence: 93%
“…These results are in good agreement with Ayadi and Grati-Kamun (2009), Malheiro et al (2009) and Jaber et al (2012) who reported more than 90% chlorophyll loss in olive oil samples.…”
Section: Araştırma Makalesisupporting
confidence: 92%
“…As it can be observed in Fig. 2 18 , which reported that enrichment of refined olive oil with phenolic compounds and chlorophyll pigments rich extract recovered from Chemlali olive leaves resulted in an appreciable resistance to oxidative deterioration. In addition, Psomiadou, & Tsimidou 19 claimed that squalene had a protective effect on the oxidative stability of olive oil due to the products of squalene oxidation are quite stable and would not be further involved in propagation reactions.…”
Section: Quality Indicesmentioning
confidence: 74%
“…Additionally, it was mentioned that the products of squalene oxidation remain unchanged over a substantial range of oxygen uptake, so that they may not strongly participate in propagation reactions. Recent work in our laboratory has shown that chlorophyll pigment recovered from Chemlali olive oil increased the oxidative stability of refined oils at the beginning of the study to attend 6 h 20 min 18 . This low stability of oils enriched with chlorophyll extract was attributed to the latter s low antioxidant capacity as reported by LanferMarquez, et al 24 Therefore, added with squalene 800 mg kg 1 could be responsible for the increase of oxidative stability of studied oils.…”
Section: Oxidative Stability Of Re Ned Oilsmentioning
confidence: 99%